Roads Disrupt Frugivory and Seed Removal in Tropical Animal-Dispersed Plants in French Guiana - Coutant, Opale; Boissier, Olivier; Ducrettet, Manon; Albert-Daviaud, Aurélie; Bouiges, Axelle; Dracxler, Caroline Marques; Feer, François; Mendoza, Irene; Guilbert, Eric; Forget, Pierre-Michel (Frontiers in Ecology and Evolution, 2022)
Ecological interactions are being affected at unprecedented rates by human activities in tropical forests. Yet, the continuity of ecological functions such as frugivory, seed dispersal and predation by animals is crucial for forest regeneration and species resilience to anthropogenic stressors. It thus becomes increasingly urgent to be able to rapidly assess the health status of these ecological processes in order to take appropriate management measures to conserve diversity in natural habitats. In this paper, we present how we monitored health of a Guianan forest based on the evaluation of the activity of vertebrate wildlife both on the ground and in the canopy, and of the fate of seeds enclosed in animal-dispersed tropical fruits. Using a method that we had previously developed to rapidly assess the activity of frugivores and granivores, we aimed at evaluating the effects of anthropogenic stressors on the health status of a mature rainforest crossed by a newly opened, 80-km asphalted road in French Guiana. We used automatic remote camera traps to identify ground- and canopy-foraging wildlife during the fruiting periods of four animal-dispersed tree species scattered in four forest patches located near (< 1 km) ecological corridors that have been preserved as canopy bridges over the road. We studied the effects of frugivore occurrence at the focal tree species by counting fallen fruits and seeds on the ground, and calculating the proportions of fruits consumed and of seeds removed (either dispersed or predated) by animals. Compared to observations at a remote, control forest, the proportions of fruits opened and consumed by fruit- and pulp-eaters, and of seeds removed by both granivores and frugivores show a steeper decrease in forest areas located near the road for plant species strictly dependent on large-bodied primates for seed dispersal than for species relying on both primates and birds. This is possibly due to compensatory effects by smaller frugivores that maintain ecological functions near the road. Therefore, despite efforts made to preserve forest continuity, anthropogenic stressors associated with road proximity are affecting wildlife occurrence and disrupting associated ecological functions that are crucial for plant regeneration, contributing to further forest degradation.